Neurofibrolipoma of the dorsum of hand: a case report - Mahipathy, Surya Rao Rao Venkata; Durairaj, Alagar Raja; Sundaramurthy, Narayanamurthy; Parthasarathy, Jayaganesh (International Surgery Journal, 2017)
Neurofibrolipoma, also called fibrolipomatous hamartoma, is a rare benign lesion which commonly involves the upper limb and its nerves with the median nerve being frequently involved. It also affects other nerves such as the ulnar, radial and brachial plexus.